Characterizing heavy ions-irradiated Zr/Nb: Structure and mechanical properties. (July 2022) - Daghbouj, N.; Sen, H.S.; Čížek, J.; Lorinčík, J.; Karlík, M.; Callisti, M.; Čech, J.; Havránek, V.; Li, B.; Krsjak, V.; Liedke, M.O.; Butterling, M.; et al.
Graphical abstract: Highlights: Mechanical and structural properties of ion (C, Si, or Cu) irradiated Zr/Nb NMMs are highly dependent on thickness and damage. Thin (Zr/Nb27) multilayer is 11% harder than the thick (Zr/Nb96) one. Irradiation hardening in Zr/Nb27 is minuscule (maximum 8 %) while a significant hardening is observed in Zr/Nb96 (maximum 24%). In Zr/Nb multilayer, the higher the interface density, the higher the strain. Abstract: In this work, the radiation responses of Zr/Nb nanostructured metallic multilayers (NMMs) are studied. The nanostructures with different layer thicknesses were deposited on Si (1 1 1) substrate by using magnetron sputtering and were subjected to heavy-ion irradiation at room temperature with different fluences. Nanoindentation, XRD, DFT, SIMS, and Variable Energy Positron Annihilation Spectroscopy (VEPAS) techniques were used to study the type and distribution of defects, and strain within the material as well as the changes in the hardness of the structures as a function of damage. Our results suggest that the strain and the irradiation hardening are layer thickness- and damage-dependent while they are independent of the type of irradiated ions. The magnitude of hardening decreases with decreasing individual layer thickness indicating that the number of interfaces has a direct effect on the radiation tolerance enhancement. For thin layers with a periodicity of 27 nm (Zr/Nb27 ), a transition from hardening to softening occurs at high fluence, and a saturation point is reached in thick layers with a periodicity of 96 nm (Zr/Nb96 ). The as-deposited thin multilayers presented a significantly higher atomic-scale disorder which increases with ion irradiation compared to the thick multilayers. VEPAS reveals the vacancy defects before and after irradiation that contribute to the presented strain. Based on the findings, thin nanostructured Zr/Nb multilayered structures possess excellent radiation resistance due to the high density of interfaces that act as sinks for radiation-induced point defects.